Amyloid formation in response to beta cell stress occurs in vitro, but not in vivo, in islets of transgenic mice expressing human islet amyloid polypeptide. - Westermark, G. (The Feinstein Institute for Medical Research, 1995)
BACKGROUND: Human, but not mouse, islet amyloid polypeptide (IAPP) is amyloidogenic. Transgenic mice overexpressing human IAPP in the beta cells of the islets of Langerhans should be useful in identifying factors important for the deposition of IAPP as insoluble amyloid fibrils. MATERIALS AND METHODS: Transgenic mice expressing human IAPP were examined using several experimental models for the production of persistent hyperglycemia, as well as for the overstimulation and/or inhibition of beta cell secretion. Obesity was induced by aurothioglucose. Persistent hyperglycemia was produced by long-term administration of glucocorticosteroids or by partial pancreatectomy. Inhibition of normal beta cell exocytosis by diazoxide administration, with or without concurrent dexamethasone injections, was carried out to increase crinophagy of secretory granules. The human IAPP gene was also introduced into the ab and ob mouse models for diabetes. Finally, isolated islets cultivated in vitro at high glucose concentration were also examined. RESULTS: No amyloid deposits were found in the pancreata of any of the animals, either by light microscopy after Congo red staining or by electron microscopy after immunogold labeling with antibodies specific for human IAPP. Aurothioglucose treatment resulted in increased numbers of granules in the beta cell and the appearance of large lysosomal bodies without amyloid. However, islets from db and ob mice expressing human IAPP cultivated in vitro in the presence of glucocorticosteroid and/or growth hormone, were found to contain extracellular amyloid deposits reacting with antibodies to human IAPP. CONCLUSIONS: Oversecretion of human IAPP or increased crinophagy are not sufficient for amyloid formation. This indicates that other factors must influence amyloid deposition; one such factor may be the local clearance of IAPP.